Rivaroxaban prescribing in a Saudi tertiary care teaching hospital - Ahmed Yacoob Mayet; Ahmed Ibrahim Alsaqer; Abdullah Musa Alhammad; Hussain Abdulrahman Al-Omar (Elsevier, 2018)
Purpose: This drug utilization review (DUR) aimed to describe the use of rivaroxaban in a tertiary care teaching hospital and to audit the hospital physicians' prescribing practice. Methods: This study reviewed rivaroxaban prescriptions for patients admitted to a tertiary care teaching hospital in Riyadh, Saudi Arabia, between October 1, 2016 and January 15, 2017. It included all in-patients who received at least one dose of rivaroxaban, using data from the hospital's health information system (HIS). Appropriateness of prescribing was evaluated based on documented indication, dosing according to the patient's renal function for each approved indication, and restriction policy as per hospital department. Results: During the study period, a total of 343 rivaroxaban prescriptions for 322 patients were identified. Overall, more than 56% of rivaroxaban prescriptions met at least one inappropriate criterion. Inappropriate dosing per patient's creatinine clearance (CrCl) was recognized in 42% of rivaroxaban prescriptions with the majority of these prescriptions issued for lower doses in 82.9% of prescriptions and non-approved indications identified in 14% of rivaroxaban prescriptions. Conclusions: The introduction of oral rivaroxaban represents a paradigm shift in anticoagulation management. Future longer, larger multi-center research is needed to identify the most effective interventions to enhance rivaroxaban knowledge translation and reduce the likelihood of inappropriate rivaroxaban prescribing and associated economic and side effects sequelae. Keywords: Rivaroxaban, Drug utilization review, Hospital, Audit, Saudi Arabia